Putusan Hakim Dalam Menuntaskan Sengketa Perkawinan Poligami Di Indonesia - Nuryamin, Nuryamin; Farid, Diana; Abdulah Pakarti, Muhammad Husni; Hendriana, Hendriana; Hilal Nu'man, Mohamad (JUSTISI, 2023)
Polygamy only applies to those who according to law and religion allow their husbands to have multiple wives. This is explained in the general description of the Marriage Law Point 4c, which states: As permissible by law and the religion concerned, a husband can have multiple wives only if the parties so desire. The court has absolute power to negotiate on the basis and conditions of the polygamy permit application and the court has the authority to try and make decisions in the form of legal considerations and reasons. The scholars, the Prophets of the Qur'an and Hadith, depending on the case. In order not to harm the parties in the proceedings, cases decided in court must have clear reasons. Courts need such evidence to determine their case. Article (1) Law Number 7 of 1989 concerning the Religious Courts regulates all court decisions with reasons, and special provisions or relevant legal written sources used as the basis for decisions.